Military duty and military construction in Dagestan in 1917–1928: a historical aspect - Ganih Shikhvalievich Kaymarazov; Leyla Ganhievna Kaymarazova (Вестник Майкопского государственного технологического университета)
The relevance of the research problem is connected with the growing interest in the historical experience of national military construction, the performance of military duties by the citizens of the Russian Federation, as well as in the issues of development of the Armed Forces of the Russian Federation that have clearly emerged recently. Using the developments of domestic and foreign historiography, based on the analysis of archival and literary sources, ego-documents and materials of periodicals, some of which are introduced into scientific circulation for the first time, using the principle of historicism, comparative historical, problem and chronological, biographical, descriptive methods, the process of national military construction and the introduction of military duty in Dagestan have studied within the designated chronological framework.Taking into account the peculiarities associated with the adherence of the population of Dagestan to local traditions and norms of Islam, the multinational composition of the region, the level of itssocial and economic, political and socio-cultural development, the historical aspect of the problem have been considered in the pre-revolutionary period, during the revolutionary events of 1917, the Civil War and intervention; the Soviet national military construction in 1920–1928 up to the first mandatory conscription of representatives of the peoples of Dagestan for active military service in the ranks of the Workers ‘and Peasants’ Red Army have been estimated. The main prospects for the further scientific development of the problem have been outlined, the results of which can be used in writing works on the history of the North Caucasus and Dagestan, preparing special courses for the humanitarian faculties of higher educational institutions, and in the practical work of state institutions and organizations.